RISK FACTORS FOR VARICOSE VEINS IN BLUE-COLLARED WORKERS AT THE GLODOK MAKMUR SHOPPING CENTRE JAKARTA - Chandra, Indah Mutia; Wardana, I Nyoman Gede; Widianti, I Gusti Ayu; Muliani, Muliani (E-Jurnal Medika Udayana, 2024)
Varicose veins, apart from affecting daily activities such as walking, also impact aesthetics. Varicose veins are dilated veins characterized by the bulging of blood vessels. In Europe, varicose veins are experienced by 50% of the population, while in Indonesia, it is around 25-30% of the population. Although varicose veins have a low mortality rate, the discomfort, swelling, and hyperpigmentation they cause can progress to more complex health problems. This study aims to determine the risk factors for lower limbs varicose veins in blue-collar workers at the Glodok Makmur shopping centre Jakarta. A case-control design was used in this research. A total of 40 cases, namely male workers with lower limb varicose veins, and 40 controls, namely male workers without lower leg varicose veins, were selected using purposive sampling. Data from respondents were collected through questionnaires and analyzed using the Chi Square test with a significance of ? = 0.05. From the results of the analysis, it was found that lower limbs varicose veins had a significant relationship with high BMI (OR = 4.667, 95% CI = 1.507-14.455), dominant working position standing (OR = 7.071, 95% CI = 2.519-19.850), smoking habits (OR = 0.648, 95% CI = 0.503-3.018), and family history of varicose veins (OR = 6.000, 95% CI = 2.207-16.313). The results of this study indicate that high BMI, dominant working position standing, smoking habit, and family history of varicose veins are potential risk factors for the occurrence of lower leg varicose veins in blue-collar workers at the Glodok Makmur shopping centre Jakarta.